Corrosion Behaviour of 304 Austenitic, 15-5PH and 17-4PH Passive Stainless Steels in acid solutions - Lara Banda, María del Refugio; Gaona Tiburcio, Citlalli; Zambrano Robledo, Patricia del Carmen; Cabral Miramontes, José Ángel; Estupiñan López, Francisco Humberto; Baltazar Zamora, Miguel Ángel; Croche B., R.; Vera V., E.; Almeraya Calderón, Facundo (Electrochemical Science Group, 2018)
The objective of this work was to study is use electrochemical techniques to determinate the growth conditions, characteristics and resistance of passive layers of stainless steel (SS): 304 austenitic, 17-4PH (precipitation hardening) and 15-5PH. Passivation of the SS was performed in 15% citric acid at temperatures of 25 and 49 °C. The corrosion kinetics was obtained using the electrochemical technique as potentiodynamic polarization (PP), in a three-electrode system. The electrolytes used were sodium chloride (5 wt. % NaCl) and sulfuric acid (1 wt. % H2SO4). Passivation in citric acid allows obtain passive layers at temperatures of 49°C with immersion times of 30 minutes. In precipitation hardening steels, passive layers up to 360 mV in sodium chloride. Can be obtained. In sulfuric acid, there is a mechanism of passivation – transpassivation - secondary passivation, this due to the high electropositive values of potential.